"Lugar de mulher é na reitoria": análise discursivo-crítica das formações identitárias e das relações de poder de mulheres do alto escalão nas IFES mineiras - Pauline Freire Pimenta (2019)
The objective of this research is to analyze the identity formation of women who made it to the top management position of public university management: as rector or vice-rector. Within a critical and discursive approach, this research seeks to look at three aspects that mark the theme: 1) women’s fight to conquer rights previously denied to them, such as working positions and management of a company or institution; 2) management and relations of power, once, to reach the top position of an institution, negotiations, articulations, productions will have to take place; and 3) the formation of these women’s identities. As a theoretical-methodological basis, the discursive-critical and explanatory studies of Norman Fairclough (2003) and Lilie Chouliaraki and Norman Fairclough (1999) will be used together with the theoretical-methodological model of Speech-oriented Discourse Analysis (ADTO), the Evaluation System, Peter White (2004) and Martin and White (2005), on a transdisciplinary character with the social categories of Feminism (being woman) and Identity (HALL, 2000, 2015; GEE, 2000). For this purpose, recorded interviews were conducted with 12 women, rectors/vice deans and former deans. The interviews were transcribed and have composed the corpus of analysis of this work. In the analysis, three different groups of discursive representations were listed: patriarchal, permeated by relations of power/legitimacy and by gender relations/resistance to patriarchal discourses, through which it was possible to perceive how the interviewees represent themselves and their multiple identities: wife, mother, woman, teacher, manager, researcher, professional and feminist appear as hybrid identities and in development. After the analysis, it was possible to realize how much the patriarchal device (SWAIN, 2014) is still latent in the reports of the interviewees, who, even while occupying prestige positions in the institutions in which they act, still see themselves as the main responsible for their private sphere. In addition, they are challenged by obstacles such as their age, area of activity, being a woman or beautiful, often needing strategies such as working a lot and well, to prove themselves competent or even to accomplish titles as Cnpq researcher 1 A to legitimize their power. A glimmer of hope comes when we come across the professional and feminist identity, when they boast of the achievements of the movement, such as being free to work and study, having the help of someone to take care of their home and their children. This shows that private space must be occupied by men as well. They also deny machismo, such as the obligation to marry and defend gender equity.